2009
DOI: 10.1007/s10495-009-0321-2
|View full text |Cite
|
Sign up to set email alerts
|

Is TRAIL the holy grail of cancer therapy?

Abstract: Inducing apoptosis has become an important approach in the development of new anti-cancer treatments. Tumour necrosis factor apoptosis inducing ligand (TRAIL) based therapies have emerged as one of the most promising examples of this as they selectively induce apoptosis in tumour cells. However, many primary tumours are inherently resistant to TRAIL-mediated apoptosis and require additional sensitisation. Here we review apoptotic and non-apoptotic TRAIL-signalling, and the therapeutic effects of TRAIL-based tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 158 publications
(165 reference statements)
2
101
0
1
Order By: Relevance
“…Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) is currently being tested as therapeutic agent for HCC treatment, but its utility is greatly hampered by the fact tumor cells ultimately develop resistant to the TRAILinduced apoptosis [6,7]. The exact mechanism(s) responsible for resistance to TRAIL is still not completely understood; however, susceptibility to TRAIL-induced apoptosis can be regulated at several levels in the apoptotic signaling cascades [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) is currently being tested as therapeutic agent for HCC treatment, but its utility is greatly hampered by the fact tumor cells ultimately develop resistant to the TRAILinduced apoptosis [6,7]. The exact mechanism(s) responsible for resistance to TRAIL is still not completely understood; however, susceptibility to TRAIL-induced apoptosis can be regulated at several levels in the apoptotic signaling cascades [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies demonstrated that TRAIL and other death ligands, including CD95/ FasL and TNF, could sensitize tumor cells for ionizing radiationand drug-induced apoptosis. Such a combined modality may circumvent the resistance of tumors against chemo-and radiotherapy (Marini and Belka, 2003;Schmelz et al, 2004;Marini et al, 2005;Fulda, 2009;Newsom-Davis et al, 2009; for review see Daniel et al, 2001). Ligands of the TNF family initiate the extrinsic apoptotic pathway through binding to cell surface death receptors of the TNF receptor superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is well established that resistance can be relieved by a poorly understood phenomenon generally referred to as 'sensitization'. A plethora of sensitizing agents, including ionizing radiation, chemotherapeutic drugs, cytokines as well as HDAC, proteosome or phosphatidylinositol-3-kinase (PI3K)/Akt inhibitors can reverse the TRAIL-resistant phenotype (Figure 3) (Altucci et al, 2001(Altucci et al, , 2005Clarke et al, 2004;Insinga et al, 2005;Nebbioso et al, 2005;Newsom-Davis et al, 2009). Furthermore, administration of inhibitors of the canonical nuclear factor-kB pathway, which has been shown to regulate resistance to TRAIL-induced apoptosis, induces sensitization of cancer cells to TRAIL (Ravi et al, 2001).…”
Section: Novel Paradigms For Cancer Therapy V Pavet Et Almentioning
confidence: 99%